Deciphering the Roles of Metformin in Alzheimer’s Disease: A Snapshot - Liao, Wang; Xu, Jiaxin; Li, Bo; Ruan, Yuting; Li, Tian; Liu, Jun (Frontiers in Pharmacology, 2022)
Alzheimer’s disease (AD) is a prevalent neurodegenerative disease predominantly affecting millions of elderly people. To date, no effective therapy has been identified to reverse the progression of AD. Metformin, as a first-line medication for Type 2 Diabetes Mellitus (T2DM), exerts multiple beneficial effects on various neurodegenerative disorders, including AD. Evidence from clinical studies has demonstrated that metformin use contributes to a lower risk of developing AD and better cognitive performance, which might be modified by interactors such as diabetic status and APOE-ε4 status. Previous mechanistic studies have gradually unveiled the effects of metformin on AD pathology and pathophysiology, including neuronal loss, neural dysfunction, amyloid-β (Aβ) depositions, tau phosphorylation, chronic neuroinflammation, insulin resistance, impaired glucose metabolism and mitochondrial dysfunction. Current evidence remains ambiguous and even conflicting. Herein, we review the current state of knowledge concerning the mechanisms of metformin in AD pathology while summarizing current evidence from clinical studies.